1997
DOI: 10.1073/pnas.94.8.3536
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interaction between DARPP-32 and protein phosphatase 1 (PP-1): DARPP-32 peptides antagonize the interaction of PP-1 with binding proteins

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 43 publications
8
88
0
3
Order By: Relevance
“…Thus, our study revealed that PP1 not only stabilizes MT attachment by dephosphorylating Aurora-B substrates at KTs 18,28-30 but also induces plate thinning by dephosphorylating Kif18A. At the same time, this finding establishes Kif18A as the first Cdk1 substrate-apart from PP1 itself [37][38][39] -that is directly dephosphorylated by PP1 demonstrating that PP1 can act as an antagonist of not only Aurora-B but also Cdk1. Dephosphorylation of Kif18A by PP1 depends on a conserved PP1-binding motif located in the Cterminus of Kif18A (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, our study revealed that PP1 not only stabilizes MT attachment by dephosphorylating Aurora-B substrates at KTs 18,28-30 but also induces plate thinning by dephosphorylating Kif18A. At the same time, this finding establishes Kif18A as the first Cdk1 substrate-apart from PP1 itself [37][38][39] -that is directly dephosphorylated by PP1 demonstrating that PP1 can act as an antagonist of not only Aurora-B but also Cdk1. Dephosphorylation of Kif18A by PP1 depends on a conserved PP1-binding motif located in the Cterminus of Kif18A (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Many of these proteins share a canonical tetrapeptide motif, RVXF, which represents an important PP1-binding domain (37,38 (11), which may approximate to the RVXF motif. However, no such sequence was found in I 1 PP2A (10), which functioned in essentially the same manner as I 2 PP2A to stimulate the histone H1 and MBP phosphatase activity of PP1 C (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…With one exception, these all exhibit the VXF motif, and only one occurrence of the VXW sequence was found. Both inhibitor-1 and DARPP-32 contain sequences at their N termini (KIQF) that are similar to the RVXF motif and that are required for inhibition of PP1 (35,36). Interestingly, the results of the random peptide screen did not yield any substitution of Val for Ile.…”
Section: Table I Alignment Of Peptide Sequences That Bind To Pp1mentioning
confidence: 99%
“…It remains a possibility that binding of variants of the PP1-binding motif could produce differential effects on either activity or substrate specificity. In this regard, it is of interest to note that both inhibitor-1 and DARPP-32 contain sequences at their N termini (KIQF) that are similar to the RVXF motif and that are required for inhibition of PP1 (35,36). Irrespective of whether occupancy of the VXF binding site can affect either activity or substrate specificity, there is support for a model in which a high affinity interaction with PP1 involves at least two binding sites of lower affinity, as has been suggested for inhibitor-1 and DARPP-32 (34 -36).…”
Section: Table I Alignment Of Peptide Sequences That Bind To Pp1mentioning
confidence: 99%